Reinventing the Sublime : Post-Romantic Literature and Theory. - Vine, Steven (Chicago : Sussex Academic Press, 2013)
Reinventing the Sublime looks at the return of the sublime in postmodernity, and at intimations of a?post-Romantic' sublime in Romanticism itself. The sublime is explored as a discourse of?invention'? taking the Latin meaning of to?come upon',?find',?discover'? that involves an encounter with the new, the unregulated and the surprising. Lyotard and Žižek, among others, have reconfigured the sublime for postmodernity by exceeding the subject-centred discourse of Romantic aesthetics, and promoting not a sublime of the subject, but of the unpresentable, the?Real', the unknown, the other.
Cover; Copyright; Contents; Acknowledgments; Introduction: Reinventing the Sublime; Part I: Romantic Totality; 1 William Blake's Materialities; 2 Mary Shelley's Bodies; 3 Thomas De Quincey's Identifications; Part II: Modernist Alterity; 4 T.S. Eliot's Intensities: The Waste Land; 5 Virginia Woolf's Disjunctions: Mrs Dalloway; 6 Djuna Barnes's Night Life: Nightwood; Part III: Postmodern Temporality; 7 Thomas Pynchon's Entropy: The Crying of Lot 49; 8 D.M. Thomas's Anamnesis: The White Hotel; 9 Toni Morrison's Belatedness: Beloved; Notes; Index.
Print version record.
JSTOR
Keywords: Sublime, The, in literature; English literature -- History and criticism; American literature -- History and criticism; Romanticism; Postmodernism (Literature); Sublime dans la littérature.; Littérature anglaise -- Histoire et critique; Romantisme; Postmodernisme (Littérature); romanticism (form of expression); LITERARY CRITICISM -- General; American literature; English literature; Postmodernism (Literature); Romanticism; Sublime, The, in literature; Criticism, interpretation, etc